PENGEMBANGAN BAHAN AJAR PEMBELAJARAN TEMA (MENYAYANGI TUMBUHAN DAN HEWAN) DENGAN MENGGUNAKAN METODE STORYTELLING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA SISWA KELAS III SEKOLAH DASAR 112327 SIRIA-RIA - Laila Sari Pohan (Universitas Negeri Semarang, 2023)
This study aims to determine how the development of teaching materials for the storytelling method on the thematic theme of loving plants and animals in class III and efforts to improve students' speaking skills in class III of Primary School 112327 Siria-Ria. This research is a type of development research (Research and Development) using the 4-D Model 4-D development model, namely defining (Define), designing (Design), developing (Develop), and disseminating (Disseminate). The subjects in this study are media expert validation and material experts and the object in this study is the development of theme learning teaching materials (loving plants and animals) using the storytelling method to improve the speaking skills of grade III elementary school students. The instrument used to collect data is a questionnaire. The results of the validation of teaching materials on learning themes (loving plants and animals) using the storytelling method are In the validation of material experts obtained 84% with very feasible criteria. And in the media expert validation obtained a score of 93% with very feasible criteria. Based on the data obtained, it can be concluded that teaching materials use the storytelling method to improve speaking skills in grade III elementary school students. Can improve the speaking skills of grade III students.